Construction and Validation of an Arabic Questionnaire on the School Dropout Factors (QSD) - ELLOUMI, Ali; CHERIF, Aicha (Advances in Social Sciences Research Journal, 2021)
This article presents the principles of construction and validation of a questionnaire on the phenomenon of school dropout by illustrating various aspects from a measurement tool prepared to study the different factors of this reality. The standardized theoretical models were adapted and completed for the needs of the study. Educational institutions and, in particular, middle school must establish a clear vision and mission regarding the training that every social professional will demand. School has always played the role of a pupil’s education, but the fact that a significant number of secondary students are abandoning their programs without having completed their course of studies, is a specific symptom of an educational crisis that is occurring within them. For this reason, the present study aimed to validate a key tool to establish the causes, whether endogenous or exogenous as to why pupils leave college without having completed their qualification. Different aspects of validation are discussed: The acceptability by studying data concerning the description of school dropout, the validity of constructing a score on the causes of school dropout, the reliability of the components of the questionnaire, the validity of the construct of the tool. The full questionnaire, with the origin of the questions, instructions for the interviewers and coding mode are presented in the methodology. The questionnaire design, consisting to determine the reasons of early dropout Tunisian pupils. The questionnaire took into account the theoretical proposals of several scientific researches. The instrument developed was validated with a sample of 750 pupils (including 675 respondents) in Tunisian colleges with a national dropout rate of 10%. The respondents (317 girls and 358 boys) have an average age of 14.11 years. The 68 items questionnaire was designed to identify, among the population of pupils quitting their school, 7 categories of factors that potentially lead to Tunisian children dropping out, Institutional, Sociological, Economic, Personal, Family, Cultural and Geographical- with their respective subcategories. Knowing the reasons why college pupils abandon a middle school in particular will allow educational actors to analyze administrative and/or academic requirements and take mitigation measures to minimize school dropout.